Galaxy Zoo: Disentangling the Environmental Dependence of Morphology and Colour - Skibba, R; Bamford, S; Nichol, R; Lintott, C; Andreescu, D; Edmondson, E; Murray, P; Raddick, M; Schawinski, K; Slosar, A; Szalay, A; Thomas, D; et al. (2008)
We analyze the environmental dependence of galaxy morphology and colour with two-point clustering statistics, using data from the Galaxy Zoo, the largest sample of visually classified morphologies yet compiled, extracted from the Sloan Digital Sky Survey. We present two-point correlation functions of spiral and early-type galaxies, and we quantify the correlation between morphology and environment with marked correlation functions. These yield clear and precise environmental trends across a wide range of scales, analogous to similar measurements with galaxy colours, indicating that the Galaxy Zoo classifications themselves are very precise. We measure morphology marked correlation functions at fixed colour and find that they are relatively weak, with the only residual correlation being that of red galaxies at small scales, indicating a morphology gradient within haloes for red galaxies. At fixed morphology, we find that the environmental dependence of colour remains strong, and these correlations remain for fixed morphology and luminosity. An implication of this is that much of the morphology--density relation is due to the relation between colour and density. Our results also have implications for galaxy evolution: the morphological transformation of galaxies is usually accompanied by a colour transformation, but not necessarily vice versa. A spiral galaxy may move onto the red sequence of the colour-magnitude diagram without quickly becoming an early-type. We analyze the significant population of red spiral galaxies, and present evidence that they tend to be located in moderately dense environments and are often satellite galaxies in the outskirts of haloes. Finally, we combine our results to argue that central and satellite galaxies tend to follow different evolutionary paths.